Role of the principles of maximum and minimum entropy production in the evolution of states tribosystems. - Aulin, V. (Problems of Tribology, 2016)
Determined that the technology associated with providing maximum durability of machine parts requiring identification and justification processes and mechanisms for implementing a state of self trybosystems. From a thermodynamic point of view of the analysis set of principles that establish the effect of self and detailed focus on the role of the principles of maximum and minimum entropy production in the evolution of states tribosystems. Revealed a range of impacts, their relationship and dependence on a combination of thermodynamic flows and forces. Grounded system reacts triathl fluctuation in energy flows and thermodynamic forces with temperature. Grounded character of evolution states triathl systems in their journey to the maximum and minimum entropy production and sale of state self depending on the amount of entropy production capacity D.Hibbsa and free energy.